Supporting Young Children's Understanding of Science. (3rd April 2022) - Jung, Myoungwhon; Conderman, Greg; Jackson, Christine
Abstract: To bolster science instruction in early childhood and elementary classrooms, teachers can implement practices that focus on big ideas, engage students in science processes, and differentiate instruction.